Planeación Agregada de Costos: Procedimientos para la PYME Manufacturera Colombiana - Torres Acosta, Jairo Humberto (Ingeniería, 2001)
The developed investigation for the generation of the procedures takes likereference mark the state of the art on the Aggregate Production Planning in the universal context and in the South American context and later on him with respectto the associated costs to the Aggregate Planning denominated by the author Aggregate Planning of Costs to end up studying to depth the behavior of the Colombian productive culture regarding the Planning, the Programming and the Control of the production and its associated costs, in paticular, the development level in the investigation and the application reached in the PYME (Small and Medium Company) in this specific fieldof the Aggregate Planning.